A Comparative Analysis of Cytoplasmic Effects on Lint Yield and Fiber Quality between CMS‐D2 and CMS‐D8 Systems in Upland Cotton. Issue 2 (1st March 2019) - Zhang, Jinfa; Abdelraheem, Abdelraheem; Stewart, James McD.
Abstract : Hybrid vigor has been extensively used in crop production based on cytoplasmic male sterility (CMS). In upland cotton ( Gossypium hirsutum L.), although CMS‐D2 has been extensively studied, the cytoplasmic effects of CMS‐D8 are currently unknown. The objectives of this study were to investigate the effects of CMS‐D8 cytoplasm using four pairs of reciprocal hybrids between a D8 restorer and four commercial cultivars, in comparison with another four pairs of reciprocal hybrids between a D2 restorer and the same cultivars. Across four crosses in four replicated field tests, the hybrids with D8 cytoplasm averaged 21% lower lint yield (LY), 10% lower lint percentage (LP), 7% lower boll weight (BW), and 11% lower micronaire (MIC) than their reciprocals with upland cytoplasm. However, the two groups of reciprocals had no overall difference for upper half mean length (UHML), uniformity index (UI), fiber bundle strength (STR), fiber elongation (ELO), and short fiber content (SFC). As a comparison, the four hybrids with D2 cytoplasm averaged 3 to 6% lower in LY, LP, BW, and ELO but improved UHML and STR by 7 to 8% and reduced MIC by 4% and SFC by 16% compared with their reciprocals with upland cytoplasm. However, D8 cytoplasm showed no significant negative effect on LY and LP in one test and on BW across the tests. It is concluded that the cytoplasmic effects from the two CMS systems are different, and CMS‐D8 presents a much greater challenge in reducing its large deleterious effects on LY before this CMS system can be used in commercial hybrid seed production.